Recognizing Predictors of Students’ Emergency Remote Online Learning Satisfaction during COVID-19 - Ivana Kovačević (MDPI AG, 2021)
In order not to lose continuity in education during COVID-19, universities mainly found the solution in Emergency remote teaching. Student satisfaction with online learning experience is one of the measures of the excellence of learning practice. Our goal was to test the hypothesis that the predictors of students’ satisfaction with emergency remote online learning are their prior experience, attitude toward online learning, their motivation, aspects of the learning situation they value (expectations), and their digital competencies. For estimating students’ satisfaction, a survey was created and disseminated, resulting with 547 responses from students of engineering education. Results showed that all students had some experience with online learning platforms and MS Teams. Attitude toward online learning in this situation was neutral, as well as the level of motivation. Their expectations were relatively high in comparison to their satisfaction with all relevant aspects of the online learning situation, while their digital competency was rather perceived as advanced. Our results showed that the prediction of the emergency remote online learning satisfaction for engineering students can be achieved based on previous positive experience with learning platform, motivation for learning in a specific situation, the importance they put to the learning achievement, and their level of digital competency.